2010
DOI: 10.1017/s0022112010003848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a geometrical surface disturbance on flow past a circular cylinder: a large-scale spanwise wire

Abstract: Flow control induced by a single wire that is attached on the outer surface and parallel to the span of a stationary circular cylinder is investigated experimentally. The Reynolds number has a value of 10 000 and the wire diameter is nearly two orders of magnitude smaller than the cylinder diameter, while being larger than the thickness of the unperturbed boundary layer forming around the cylinder. A technique of high-image-density particle image velocimetry is used to characterize mean and unsteady structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
15
32
0
Order By: Relevance
“…6(a) depicts the autospectral density S u of streamwise velocity signals obtained from the present CTA measurements at selected wire locations (θ). Note that this case is analogous to the cylinder-wire configuration previously studied in the PIV investigation of Ekmekci and Rockwell (2010). As evident from Fig.…”
Section: A Comparison With Previous Findingssupporting
confidence: 52%
See 1 more Smart Citation
“…6(a) depicts the autospectral density S u of streamwise velocity signals obtained from the present CTA measurements at selected wire locations (θ). Note that this case is analogous to the cylinder-wire configuration previously studied in the PIV investigation of Ekmekci and Rockwell (2010). As evident from Fig.…”
Section: A Comparison With Previous Findingssupporting
confidence: 52%
“…To establish a baseline for this study, first, in Section 3.1, the spectral nature of CTA signals is evaluated and compared with the earlier PIV findings for a cylinder fitted with a spanwise wire identical in size to the one used in the previous investigations of Ekmekci (2006) and Ekmekci and Rockwell (2010) under identical Reynolds number condition. After this comparison, the subsequent two sections (Sections 3.2 and 3.3) will aim for an understanding of the effects of the wire size and Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by Honohan [53], the reduction in the width of the wake (and in pressure drag) by the synthetic jet and the obstruction is accompanied by suppression of vortex shedding in the near wake and a significant reduction in Reynolds stresses within the boundary layer upstream of separation. In a recent investigation of the flow past a circular cylinder (Re D = 10 4 ) with a surface-mounted wire (diameter larger than the thickness of the base-flow boundary layer), Ekmekci & Rockwell [68] reported that the near wake can significantly broaden or contract depending on the azimuthal position of the wire. Broadening was associated with bistable oscillations of the separating shear layer (on a time scale that is longer than that of the Kármán vortex shedding), and contraction occurs when the Kármán vortices are suppressed.…”
Section: (A) Trapped Vorticity Concentrations Induced By Synthetic Jementioning
confidence: 99%
“…4. The results for the 2D symmetrically (Alam et al, 2010) and asymmetrically (Ekmekci and Rockwell, 2010) tripped cases, in contrast to the case AR = 6, show that the length of the vortex formation region decreases from a = 55°(<a c ) to a = 60°(>a c ). This difference highlights the importance of the mass flux contribution due to the tip flow on the organisation of the wake structure in the three dimensional geometry.…”
Section: Velocity Field In the Wakementioning
confidence: 92%
“…They also reported bi-stable regimes when the boundary layer was transitional. Ekmekci and Rockwell (2010), for a nominally two-dimensional cylinder and wire of 0.02D at Re % 10 4 show that a change in shedding structure occurs about a critical angle of 50°< a c < 60°. They report that the transition is non-monotonic (expansion and contraction of the wake) at the extremes of the critical angle range.…”
Section: Introductionmentioning
confidence: 91%